Study on Chatushkas of Charaka Samhita w. s. r. to Bheshaja Chatushka and its Clinical Importance - Sanjana Anil Sonamale; Archana Dhanpal Jugale (AYUSHDHARA, 2025)
Charak Samhita is an ancient Indian text that forms a cornerstone of Ayurvedic medicine. It is one among the Brihattrayee. Charak Samhita is a comprehensive that covers all eight branches (Ashtanga) of Ayurveda. The text is divided into eight major sections known as Sthanas: Sutra Sthana, Vimanasthana, Sharira Sthana, Nidan Sthana, Indriya Sthana, Chikitsa Sthana, Kalpa Sthana, and Siddhi Sthana. The Sutra Sthana is the very first section which deals with the fundamental principles of Ayurveda. It provides essential guidelines on preventive healthcare, diagnosis, and treatment strategies. It consists of 30 chapters, which are further categorized into seven Chatushka having groups of four chapters each. The final two chapters of the Sutra Sthana are known as Sangraha Dwaya. The seven Chatushkas are namely Bhesaja Chatushka, Swastha Chatushka, Nirdesha Chatushka, Kalpana Chatushka, Roga Chatushka, Yojana Chatushka, Anna Pana Chatushka, etc. Among these, the Bhesaja Chatushka plays a crucial role in disease management. It mainly focuses on Roga, Rogi, Bhaishjya and Dravya, forming the foundation of Ayurvedic therapeutic applications. This study aims to explore the concept of Chatushkas in the Charak Samhita, with a special emphasis on the Bhesaja Chatushka and its clinical significance. The findings promote the integration of Ayurveda into mainstream healthcare and support the development of more effective and holistic treatment strategies.